More- Versus Less-Intensive Lipid-Lowering Therapy: Systematic Review and Meta-Analysis. Issue 8 (August 2019) - Toyota, Toshiaki; Morimoto, Takeshi; Yamashita, Yugo; Shiomi, Hiroki; Kato, Takao; Makiyama, Takeru; Nakagawa, Yasuaki; Saito, Naritatsu; Shizuta, Satoshi; Ono, Koh; Kimura, Takeshi
Abstract : Background: It has not been yet adequately addressed whether the addition of the nonstatin LDL-C (low-density lipoprotein cholesterol)-lowering agents on top of statins has the same magnitude of risk reduction in the cardiovascular events as compared with more-intensive statin therapy. Methods and Results: We performed a systematic review and meta-analysis of RCTs (randomized controlled trials) comparing more- versus less-intensive lipid-lowering therapy (LLT) on clinical outcomes in patients with atherosclerotic cardiovascular risk. We included 23 studies involving 133 037 patients (more-intensive LLT: 67 691 patients and less-intensive LLT: 65 346 patients). We evaluated 3 types of more- versus less-intensive LLT including more versus less statins (57 672 patients), combination therapy of ezetimibe versus statins alone (20 688 patients), or a PCSK9 (proprotein convertase subtilisin-kexin type 9) inhibitor with statins versus statins alone (54 677 patients). The odds for major adverse cardiovascular events (MACE; equivalent to the composite of coronary heart death, nonfatal myocardial infarction, stroke, or coronary revascularization) were significantly lower in the more-intensive LLT group compared with the less-intensive LLT group in the entire study population (odds ratio, 0.84; 95% CI, 0.79–0.88; P <0.001), and in all the 3 categories of more-intensive LLT strategies (more-intensive statin therapy: odds ratio, 0.83; 95% CI, 0.76–0.90; P <0.001, ezetimibe: odds ratio, 0.90; 95% CI, 0.85–0.96; P <0.001, and PCSK9 inhibitors: odds ratio, 0.81; 95% CI, 0.73–0.90; P <0.001) with numerically greater relative odds reduction by more-intensive statin therapy and PCSK9 inhibitors than by ezetimibe. Odds reduction for MACE per 20 mg/dL LDL-C reduction was also different across the 3 types of more-intensive LLT (more-intensive statin therapy: 17.4%, ezetimibe: 11.0%, and PCSK9 inhibitors: 6.6%). Conclusions: In this meta-analysis, more-intensive LLT as compared with less-intensive LLT was associated with significant odds reduction for MACE in the entire study population and in all the 3 categories of more-intensive LLT such as more-intensive statin therapy, ezetimibe, and PCSK9 inhibitors. However, overall odds reduction for MACE and odds reduction for MACE per 20 mg/dL LDL-C reduction were different across the 3 types of more-intensive LLT. Registration: URLs:https://www.crd.york.ac.uk/PROSPERO/ andhttp://www.umin.ac.jp/ctr . Unique identifiers: PROSPERO: CRD42018081196, and UMIN-CTR: R000036229. Abstract : Supplemental Digital Content is available in the text.